Bacteria enable tolerance to bile salt exposure in an immune-competent human intestinal model - Yuan Li; Chia-Ming Wang; Peng Zhao; Matthew T. Fernez; Rebecca L. Carrier (Gut Microbes)
Bile salts (BS) are known to be highly important in modulating bacteria-host crosstalk in the gut, serving as essential signaling molecules governing intestinal homeostasis. However, understanding of this crosstalk is limited by challenges of analyzing the mucosal interface in vivo and a lack of in vitro intestinal models incorporating bile, bacteria, and host cells. In this study, the impact of bile micelles on an in vitro intestinal model integrating commensal microbes with immune-competent human duodenal epithelium was studied. Physiological concentrations of BS/phosphatidylcholine (PC) micelles comprising a model bile were damaging to epithelial cells under hypoxic but not normoxic conditions. However, incorporation of a commensal bacterial consortium protected the epithelium from bile micelle-associated damage, as reflected in increased epithelial cell viability and preserved monolayer barrier function. Furthermore, the model bile enabled homeostasis when bacterial consortia were incorporated into epithelial-immune co-cultures, reducing barrier damage and inflammatory response induced by the consortia and modulating bacterial growth. In considering factors lacking in vitro that may promote homeostasis when intestinal tissue is exposed to bile and bacteria, we investigated the influence of mucus on bacteria-bile-epithelial/immune crosstalk by adjusting mucus thickness using air–liquid interface culture. Thicker mucus layers not only impacted the growth of consortium strains, resulting in enhanced growth of the mucin metabolizer Bifidobacterium longum, but also reduced inflammatory responses to bacteria and bile-induced epithelial damage. Overall, this study introduces a human immune-competent intestinal model capturing key features of bacteria-bile-mucosal crosstalk. Studies conducted with this system demonstrated the importance of oxygen levels, commensal microbes, and the mucus barrier in maintaining homeostasis in the small intestinal mucosa in the context of bile micelle exposure.